Development of the whole tomato and olive-based food supplement enriched with anti-platelet aggregating nutrients. Issue 2 (June 2023) - Pulcinelli, Fabio; Curreli, Mariaignazia; Natali, Pier Giorgio; Quaresima, Virginia; Imberti, Luisa; Piantelli, Mauro
Background: Platelet dysfunctions are shared by cardiovascular diseases and a wide range of inflammatory diseases. Aims: To determine the ability of a new whole tomato-based food supplement (WTBFS) containing carotenoid and olive polyphenols to inhibit platelet aggregation. Methods: Aggregation was evaluated in platelet-rich plasma using microtiter plates and a plate reader. Results: Platelets treated with WTBFS showed a >70% reduction of 5 µM adenosine diphosphate (ADP)-induced platelet aggregation; at 10 µM of ADP, the inhibitory effect of WTBFS was reduced of about 50%. Similarly, 78% and 48% reduction were obtained using 5 µg/mL and 10 µg /mL of collagen as an agonist Conclusion: Since the compounds in WTBFS share the ability to inhibit STAT3, the inhibition of its signaling pathway may represent the mechanism underlying the antiplatelet activities. The activity of a lipophilic solution prepared from WTBS was in vitro tested on the platelet aggregation in response to ADP agonists and Collagen.